Kolonisationsphasen und Kulturlandschaftswandel im Südosten der Provinz Québec (Kanada) - Pletsch, Alfred (ERDKUNDE, 1980)
The development of the cultural landscape in the south eastern portion of the province of Quebec is marked by a phase-like expansion process during the colonization epoch. Land grants (Seigniors) were handed out in the St. Lawrence Lowlands during the settlement periods of the French (1608-1663 and1663-1763), while in the following period of English rule parts of the Appalachian regions (Eastern Townships) were settled. Starting in the middle of the 19th century, French Canadians also migrated into the English speaking areas and continued this movement well into the 20th century. This agricultural expansion of the French was carried out under the influence and with the support of the church and extended geographically into the ecological marginal areas of the United States border region, as well as into the swampy lowlands of the St. Lawrence, specifically the 'Bois Francs' area. In this way the expansion and extension of the agricultural frontier continued well into recent times. The community of Villeroy in Comte Lotbiniere can be viewed as a typical example of this most recent colonization period. Soon after being established, its economic activities changed from agricultural ones to non-agricultural ones in order to take advantage of the many non-agricultural employment opportunities found in the nearby small and medium sized cities. As a result, the land is usually neglected while the farm houses continue to be used as living quarters. Somewhat different is the settlement process in the Ditton and Emberton townships where, after a rapid growth in population in the second half of the 19th century, out migration recurred. We now have here an abandonment of the land as well as the settlement itself. The two case studies examined in this article illustrate the recent predominant changes of the agricultural landscape in Quebec which, as a whole, is characterised by a marked farm-concentration as well as by a major change in the employment structure of the rural population.